Public-Private Institutions as Catalysts of Upgrading in Emerging Market Societies - McDermott, Gerald A.; Corredoira, Rafael A.; Kruse, Gregory (Academy of Management Journal, 2009)
In this article, we argue that the ability of a firm to access a variety of knowledge resources and, in turn, upgrade its products depends on its being tied not simply to any or many organizations and institutions, but rather to those that act as social and knowledge bridges between previously isolated producer communities. Through a multimethod analysis of the recent transformation of the Argentine wine industry, we highlight how distinct governance rules for new government support institutions can anchor their multiplex, cross-cutting network qualities, which underpin their ability to provide improved collective resources and reshape the ties between firms.